2021
DOI: 10.1002/mde.3311
|View full text |Cite
|
Sign up to set email alerts
|

Gender spillovers from supervisory boards to management boards

Abstract: This study investigates gender spillovers from women on supervisory boards to women on management boards in a two‐tier system with employee codetermination. The supervisory board consists of a nominating committee mainly responsible for the appointment of directors in the management board. By combining similarity attraction theory with power theory, we predict that only female shareholder representatives who serve on the nominating committee drive the positive effect on the presence of women on management boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 80 publications
3
17
0
Order By: Relevance
“…These results indicate that, in general, female independent directors bring different skills, values, and experiences to the board, thereby providing increased access to resources and connections to the external environment, as postulated by resource dependence theory (Hillman et al, 2007; Post & Byron, 2015; Wahid, 2018). Our finding is in line with previous studies, which have also found that female independent directors are better monitors (Bozhinov et al, 2021) and attend more board meetings than their male counterparts (Adams & Ferreira, 2008, 2009, 2012). The positive but nonsignificant result found in Indonesia, where the institutional environment is less developed and weaker in governance, suggests that a less diverse board with fewer female independent directors reduces their influence, causing female independent directors to have less “voice.” Hence, they are unable to lobby for a higher board meeting frequency (Schwartz‐Ziv, 2017; Usman et al, 2018).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results indicate that, in general, female independent directors bring different skills, values, and experiences to the board, thereby providing increased access to resources and connections to the external environment, as postulated by resource dependence theory (Hillman et al, 2007; Post & Byron, 2015; Wahid, 2018). Our finding is in line with previous studies, which have also found that female independent directors are better monitors (Bozhinov et al, 2021) and attend more board meetings than their male counterparts (Adams & Ferreira, 2008, 2009, 2012). The positive but nonsignificant result found in Indonesia, where the institutional environment is less developed and weaker in governance, suggests that a less diverse board with fewer female independent directors reduces their influence, causing female independent directors to have less “voice.” Hence, they are unable to lobby for a higher board meeting frequency (Schwartz‐Ziv, 2017; Usman et al, 2018).…”
Section: Resultssupporting
confidence: 93%
“…For example, female independent directors bring fresh viewpoints and tend to be more independent in their thinking than their male peers because they are not a part of the “old boys' club” (Carter et al, 2003; Fan et al, 2019). In addition, female independent directors allocate more effort to monitoring activities (Adams & Ferreira, 2008, 2009; Bozhinov et al, 2021), because women are generally more risk averse and less tolerant of opportunistic behaviors than men (Huang & Kisgen, 2013; Jiang et al, 2016). In fact, Adams and Ferreira (2009) found that female directors have better attendance in meetings and are more likely to attend monitoring‐related committees than male directors.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some works underline that female leadership could be a limiting factor for the fulfillment of business objectives [66,67] and that the exercise of their functions could assume negative traits. Other researchers, such as [68], emphasize instead the positive perception related to female leadership, which is characterized by personal security, independence, altruism, the entrepreneurial woman capable of creating change, and the ability to transform work into a vocation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, spillover effects were found from state government spending unrelated to sport [41] and state government quality (macro level) [43] on individual sport participation (micro level). In the corporate sector, positive spillover effects regarding gender diversity within a company were found to occur from women on supervisory boards to women on management boards [44]. Other studies reported negative spillover effects from the share of women in higher job levels to the share of women in lower job levels [45], suggesting that empirical evidence regarding gender diversity related to spillover effects is not consistent.…”
Section: Multi-level Perspective and Spillover Effectsmentioning
confidence: 98%